Applications and Usability of Interactive Television : 6th Iberoamerican Conference, jAUTI 2017, Aveiro, Portugal, October 12-13, 2017, Revised Selected Papers /: 6th Iberoamerican Conference, jAUTI 2017, Aveiro, Portugal, October 12-13, 2017, Revised Selected Papers. (2018) - Unknown
No abstract available